EVALUATING ANTIOXIDANT PROPERTIES OF HOMEOPATHIC FUCUS VESICULOSUS IN DPPH AND NITRIC OXIDE RADICAL SCAVENGING ASSAYS (CAHIERS MAGELLANES-NS, 2024)
The body has a complex antioxidant defence grid that relies on endogenous enzymatic and non-enzymatic antioxidants. Antioxidant represents the ability to inhibit all molecules having high red potential which makes them destructive for body structures. These molecules act against free radicals to resist their damaging effects to vital biomolecules and ultimately body tissues. The body’s defense against oxidative stress relies on a complex network of endogenous enzymatic and non-enzymatic antioxidants. These antioxidants play a crucial role in neutralizing free radicals, which can cause significant damage to vital biomolecules and tissues. This study evaluates the antioxidant activity of the homeopathic remedy Fucus vesiculosus using two established assays: the DPPH (2,2-diphenyl-1-picrylhydrazyl) and Nitric Oxide Radical Scavenging assays. In the DPPH assay, Fucus vesiculosus exhibited significant free radical scavenging activity, with a maximum inhibition of 95.37% at a concentration of 80 µl. In the Nitric Oxide Scavenging assay, the remedy demonstrated a moderate scavenging effect, with a maximum inhibition of 32.94% at the same concentration. These results suggest that Fucus vesiculosus possesses notable antioxidant properties, which could contribute to its therapeutic efficacy in homeopathic practice. Further studies are recommended to explore its potential in mitigating oxidative stress-related conditions.